PENGARUH MODEL PROJECT CITIZEN DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN TERHADAP PENANAMAN NILAI-NILAI ANTI KORUPSI SISWA SMA PADA KONSEP SISTEM HUKUM DAN PERADILAN NASIONAL - Efi Miftah Faridli (Khazanah Pendidikan, 2011)
Corruption is our national problem that we have to overcome this attitude start from little things in our clayly activity, project citizen model in every school could have our society especially for our senior high school to understand the habit of corruption with civic education in school.This research conducted with quantitative research by quasi experiment method. Analysis of this research consist of : 1) Seen that Project citizen in Civic education promoted Significant face with anti corruption values, 2) thus there are significant differences between students anti corruption values that use the project citizen model and without treatment. Key Words:: Civic Education, Project Citizen, Anti Corruption Values